2007
DOI: 10.1016/j.bbrc.2006.11.137
|View full text |Cite
|
Sign up to set email alerts
|

In vitro transformation of mesenchymal stem cells by oncogenic H-rasVal12

Abstract: Tissue stem cells may serve as progenitors for malignant tumors derived from the same tissue. Here, we report the establishment of immortalized human mesenchymal stem cells (ihMSC) and tested the feasibility of using ihMSC as presarcomatous cells. Immortalization was achieved by introducing the genes for human telomerase reverse transcriptase and Bmi1. ihMSC retained the potential for multi-directional differentiation of the original MSC. To transform ihMSC, we introduced an oncogenic H-ras(Val12) gene, and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…This observation suggests that the loss of accurate regulation of the cell cycle may be key in the transformation process. In fact, alterations in p16, p53, and p21 have been detected in transformed MSCs (23,24,42). We have previously reported that the loss of heterozygosity of p53 induced tumoral transformation in p21 −/− MSCs, and that this process was accompanied by karyotypic instability and the loss of p16 (26).…”
Section: Discussionmentioning
confidence: 97%
“…This observation suggests that the loss of accurate regulation of the cell cycle may be key in the transformation process. In fact, alterations in p16, p53, and p21 have been detected in transformed MSCs (23,24,42). We have previously reported that the loss of heterozygosity of p53 induced tumoral transformation in p21 −/− MSCs, and that this process was accompanied by karyotypic instability and the loss of p16 (26).…”
Section: Discussionmentioning
confidence: 97%
“…In one of these models, the process of transformation of hMSCs is associated with a gradual increase in genomic hypomethylation, although this phenomenon is not necessary for transformation [43]. Using an alternative approach, another group succeeded in transforming hMSCs through ectopic expression of hTERT, H-RAS and BMI-1, which inhibits the expression of genes controlled by polycomb response elements including p16 INK4A [44]. It was also reported that some hTERT-transduced hMSC lines lose contact inhibition, acquire anchorage-independent growth and form tumors in mice after long-term in vitro culture [45].…”
Section: Cell Cycle Control In Msc-based Sarcoma Modelingmentioning
confidence: 99%
“…This transformation process was associated with the deletion of the Ink4a/ARF locus and with the acquisition of an activating mutation in K-RAS. Overall, in vivo tumors originated from most of these transformed hMSCs were classified as undifferentiated spindle cell sarcomas [41,42,44].…”
Section: Cell Cycle Control In Msc-based Sarcoma Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOS, YaFuSS and an immortalized hMSC (ihMSC) line were established in our laboratory as described previously (Aoyama et al, 2004;Ishibe et al, 2005;Shima et al, 2007) Production of anti-AFAP1L1 polyclonal antibody The polyclonal antibody for AFAP1L1 was raised by immunizing rabbits with glutathione S-transferase-fused polypeptides corresponding to codon 35-113 of the human AFAP1L1 gene and purified with standard protocols using affinity columns.…”
Section: Clinical Samplesmentioning
confidence: 99%